Case report: A rare case of chondrosarcoma-like malignant giant cell tumor in adolescent rib: diagnostic challenges and treatment - Qin, Zhuolin; Li, Longqian; Jing, Tao; Wang, Cheng (Frontiers in Oncology, 2025)
Chondrosarcoma-like malignant giant cell tumor (GCT) of the rib is an extremely rare and aggressive tumor, particularly in adolescents. This case report describes a 19-year-old female presenting with a GCT of the rib with chondrosarcomatous differentiation, highlighting the challenges posed by its unusual location and pathological complexity. Multidisciplinary diagnostic approaches, including advanced imaging, immunohistochemistry (IHC), and pathology, were essential for confirming the diagnosis. Key IHC markers such as Vimentin, SMA, and CD163, alongside genetic analysis excluding H3F3A mutations, guided the diagnostic process. The patient underwent successful surgical resection, achieving early recovery without adjuvant therapy. This report underscores the importance of early detection, precise pathological evaluation, and individualized surgical treatment for rare and high-risk tumors, emphasizing the need for long-term follow-up to monitor recurrence.